Upaya Peningkatan Hasil Belajar Siswa Mata Pelajaran IPA Materi Daur Air dan Peristiwa Alam Melalui Metode Eksperimen dengan Alat Bantu Media Audio Visual di SD Muhammadiyah Boja - Widyanarko, Rudy (Universitas Sebelas Maret, 2020)
This classroom action research was used to measure the learning outcomes of science students on water cycle material and natural appearances consisting of pre-cycle, cycle 1, and cycle 2. the interaction of teachers with students is still monotone, so it is proven that the student learning outcomes of 23 students, who completed only 5 students or 21.73% and the average grade of 57.39. Improvements to cycle 1 were carried out by applying the experimental method with audio-visual media tools, with practicum activities and group discussions, only then there was a change in learning outcomes from 5 students who completed to 11 students who completed with a percentage of 47.82% and an average score class 64.56. Then the repair was carried out again with cycle 2, where researchers made improvements by further increasing motivation and guidance to students and further optimizing audio-visual media appropriately, finally student learning outcomes where all students were able to achieve complete scores with a 100% completeness percentage and an average score. the class reached 79.13. The conclusion is that the application of the experimental method (experimental) with audio-visual media aids succeeded in improving the learning outcomes of class V students in the second semester of SD Muhammadiyah Boja, Boja District, Kendal Regency for the 2019/2020 school year.